(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Net Interest Margin (NIM) and Non-Performing Loan (NPL) on profitability, as measured by Return on Equity (ROE), at PT Bank Rakyat Indonesia (Persero) Tbk during the 2010–2024 period. The research employed an associative quantitative approach using secondary data obtained from the company’s annual financial statements. Data were analyzed using classical assumption tests, multiple linear regression analysis, t-tests, F-tests, correlation coefficients, and coefficients of determination with the assistance of SPSS version 22. The results indicate that, partially, Net Interest Margin (NIM) does not have a significant effect on Return on Equity (ROE), while Non-Performing Loan (NPL) has a significant effect on Return on Equity (ROE). Simultaneously, NIM and NPL have a significant effect on ROE. The coefficient of determination of 67.9% indicates that variations in ROE can be explained by NIM and NPL, while the remaining 32.1% is influenced by other factors outside the research model. These findings suggest that credit risk management and the bank’s ability to generate interest income are important factors in improving corporate profitability.